Women of color in higher education changing directions and new perspectives - Lloyd-Jones, Brenda; Jean-Marie, Gaetane; Frierson, Henry T. (Henry Taylor), 1944-; Tate, William (Bingley, U.K. : Emerald, 2011)
Ask practically any academic department chair why they do not have more African Americans among faculty members and they generally respond with stock stories or folktales, which stimulated the title of this volume. Stock stories are akin to grand narratives that explain'why things are' in ways that satisfy those in dominant positions. Frierson and Tate argue it is time to move beyond these. The purpose of the book is to provide historical, conceptual, and empirically-based analyses focused on the development of African Americans in STEM fields. There is rarely any real understanding of the uneven contours of the education pipeline or the transition to academic life experienced in these situations and this volume will shed light on opportunities to advance African American attainment in STEM disciplines throughout the academic and professional spectra, and the mitigation of disparities that continue to be so prevalent. The editors hope that it will generate discussions and actions that are based on empirical evidence and policy analyses, rather than long standing stock stories and folktales that misrepresent the paths linked to African Americans attainment in STEM fields.
Prologue / Olga M. Welch -- Women of color in higher education in the 21st century / Ga$1#0B(Bane Jean-Marie -- ch. 1. Diversification in higher education administration : leadership paradigms reconsidered / Brenda Lloyd-Jones -- ch. 2. Diversity in sport : the status of African American female head coaches and administrators in collegiate athletics / Vicki A. Williams -- ch. 3. Women of color faculty : recruitment, hiring, and retention / Norma T. Mertz -- ch. 4. Promoting attainment of African American women in the STEM fields : lessons from historically black colleges and universities / Marybeth Gasman, Laura W. Perna -- ch. 5. Mentoring and supportive networks for women of color in academe / Ga$1#0B(Bane Jean-Marie, Jeffrey S. Brooks -- ch. 6. Mentoring and interim positions : pathways to leadership for women of color / Jothany Blackwood, Sharon Brown-Welty -- ch. 7. Their rightful place : diversity narratives, women of color agency and transformation of the academy / Venice Thandi Sul-- ch. 8. Asian American Pacific Islander women from Ph. D. to campus president : gains and leaks in the pipeline / Edith Wen-Chu Chen, Shirley Hune -- ch. 9. The unwritten rules of the academy : a balancing act for women of color / Natasha A. Mitchell, Jaronda J. Miller -- ch. 10. Female faculty of color : successful strategies in academia / Lisa R. Bass, Susan C. Faircloth -- ch. 11. Female faculty of color : agency and structure in race research / Benjamin Baez -- ch. 12. Building bridges for women of color in the professoriate / Vinetta C. Jones -- ch. 13. Star light, star bright : a black female scholar seeks to find'voice' in the academy / Latish C. Reed -- ch. 14. Poised to shatter the glass ceiling in the ivory tower / Mary V. Alfred -- ch. 15. Nurturing intellectual voices :'stirring up' conversations about cultural competence in the university classroom / Carolyn Walker Hopp -- ch. 16. Mentoring transformed : when students of color see diversity in leadership / Milagros Pe, JeffriAnne Wilder -- Epilogue / Brenda Lloyd-Jones, Ga$1#0B(Bane Jean-Marie.s
Includes indexes.
Keywords: Education -- Multicultural Education; Education -- Professional Development; Multicultural education; Teaching staff; Sex discrimination in higher education; Women -- Education (Higher)